The Breakthrough Agenda Report 2024 - Agriculture - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
Agriculture is a significant source of global greenhouse gas (GHG) emissions, and food systems contribute to nearly one-third of global emissions. The Breakthrough Agenda Report 2024 – Agriculture highlights the need for stronger international collaboration to transform the sector into a more climate-resilient, low-emissions system that meets other societal and environmental goals.